Monitoring Tegangan dan Arus Menggunakan LoRa (Long Range) Pada Sistem PJUTS - Ifnil, Anur; Rozie, Fachrul; Rizaldi, Jimmi; Akhdiyatul, Akhdiyatul (Electrical Network Systems and Sources, 2024)
This project aims to design and construct an efficient and monitoring volatge sustainable Public Street Lighting System (PSLS) in the Muara Pawan Subdistrict, Sukamaju Village. The system design includes the implementation of LoRa technology for monitoring voltage and current to enhance energy management efficiency. The project also takes into account the lighting needs along strategically positioned public roads. In this design, we will focus on environmentally friendly and energy-efficient types of lighting, integrating automatic sensors to adjust brightness levels according to environmental conditions. The use of LoRa technology will enable long-distance data transmission, minimizing field maintenance needs and improving monitoring and maintenance efficiency. The project will also consider data security aspects in transmitting monitoring information, ensuring compliance with applicable regulations and standards. It is anticipated that the implementation of the proposed PSLS will provide a significant improvement in public street lighting, positively impacting community safety, and supporting efforts to create a more sustainable environment in the Muara Pawan Subdistrict, Sukamaju Village.’ Keywords: Monitoring Voltage and Current with LoRa (Long Range), LoRa.